EPIDEMIOLOGI MANAJERIAL DAN DETERMINAN SOSIAL DI RUMAH SAKIT RUJUKAN: TINJAUAN LITERATUR MODEL PENINGKATAN KINERJA MELALUI KEPEMIMPINAN DAN PROMOSI JABATAN DI RSUD PROVINSI NTB - Lalu Herman Mahaputra; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2026)
Improving the performance of referral hospitals in the health transformation era highly depends on the integration of managerial epidemiology and an understanding of social determinants of health. This study aims to formulate a strategic model for improving employee performance at RSUD Provinsi NTB by analyzing the roles of leadership and job promotion systems. The research method employed is a Systematic Literature Review (SLR), examining scientific articles from Scopus and Google Scholar databases within the 2014-2024 period. The literature review results indicate that transformational leadership is a determinant factor capable of mitigating workload pressure in referral hospitals, while a merit-based job promotion system acts as the primary catalyst for employee motivation and loyalty. The synthesis of the literature confirms that an effective performance model integrates epidemiological data for resource allocation with transparent human resource development policies. The implications of this study suggest that the management of RSUD Provinsi NTB should strengthen the managerial competence of middle-level leaders and standardize promotion mechanisms to respond to complex public health challenges in the West Nusa Tenggara region